1991
DOI: 10.1139/b91-056
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi of red alder (Alnus rubra) leaves and twigs in British Columbia

Abstract: A study was designed to isolate potentially pathogenic, endophytic fungi of red alder (Alnus rubra). Apparently healthy leaves and 2- to 3-year-old twigs were collected at three and eight sites, respectively, surface sterilized, cut into small pieces, and incubated on 2% malt extract agar. Ninety percent of the leaves and more than 80% of the twigs were colonized by endophytic fungi; 40 different fungi were isolated and identified. Fungi previously recorded as plant pathogens dominated the endophyte community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 4 publications
5
31
1
1
Order By: Relevance
“…For example, the isolation frequency of this species was only 3% on leaves of Acer macrophylla (Sieber and Dorworth 1994), and this species was absent from leaves of Alnus rubra and Rubus spp. (Sieber et al 1991;Shamoun and Sieber 2000). The frequent occurrence of species in Epicoccum, Cladosporium, Alternaria, and Sclerotinia sclerotiorum was consistent with the result of S. controversa Mori 2004, 2005;Osono et al 2004a).…”
Section: Discussionsupporting
confidence: 77%
“…For example, the isolation frequency of this species was only 3% on leaves of Acer macrophylla (Sieber and Dorworth 1994), and this species was absent from leaves of Alnus rubra and Rubus spp. (Sieber et al 1991;Shamoun and Sieber 2000). The frequent occurrence of species in Epicoccum, Cladosporium, Alternaria, and Sclerotinia sclerotiorum was consistent with the result of S. controversa Mori 2004, 2005;Osono et al 2004a).…”
Section: Discussionsupporting
confidence: 77%
“…In southern Sweden, Nordén et al (2004) examined fungi fruiting on fine and coarse dead wood (using a 10-cm diameter limit) in a temperate broadleaf forest and determined that 75% of ascomycetes and 50% of red-list species were found on fine dead wood. Fungal endophytes that live within plant leaves and twigs are ubiquitous and diverse (Saikkonen 2007) and can be very habitat-specific; for example, leaves of birch and alder have been found to host entirely different communities of fungal endophytes than twigs of the same plants (Sieber et al 1991, Barengo et al 2000. Sherwood and Carroll (1974) documented 25 microfungi fruiting on needles and twigs from just a few Douglas-fir trees.…”
Section: Implications Of the Intensification Of Biomass Removal For Bmentioning
confidence: 99%
“…It was demonstrated that most endophytes are able to utilize, at least in vitro, most plant cell components. Most of investigated endophytes utilize xylan and pectin, show lipolytic activity and produce non-specific peroxidases and laccases (Sieber et al 1991;Leuchtmann et al 1992), chitinase ) and glucanase (Moy et al 2002). Endophyte may be a novel and good producer of xylanase (Suto et al 2002).…”
Section: Significance Of Endophytic Microorganismsmentioning
confidence: 99%